Prescribing patterns of psychotropic medications and clinical features in patients with major depressive disorder with and without comorbid dysthymia in China. (19th October 2016) - Feng, Yuan; Sha, Sha; Hu, Chen; Wang, Gang; Ungvari, Gabor S.; Chiu, Helen F.K.; Ng, Chee H.; Si, Tian‐Mei; Chen, Da‐Fang; Fang, Yi‐Ru; Lu, Zheng; Yang, Hai‐Chen; et al.
Abstract: Introduction: Little has been reported about the demographic and clinical features of major depressive disorder (MDD) with comorbid dysthymia in Chinese patients. This study examined the frequency of comorbid dysthymia in Chinese MDD patients together with the demographic and clinical correlates and prescribing patterns of psychotropic drugs. Methods: Consecutively collected sample of 1178 patients with MDD were examined in 13 major psychiatric hospitals in China. Patients' demographic and clinical characteristics and psychotropic drugs prescriptions were recorded using a standardized protocol and data collection procedure. The diagnosis of dysthymia was established using the Mini International Neuropsychiatric Interview. Medications ascertained included antidepressants, antipsychotics, benzodiazepines, and mood stabilizers. Results: One hundred and three (8.7%) patients fulfilled criteria for dysthymia. In multiple logistic regression analyses, compared to non‐dysthymia counterparts, MDD patients with dysthymia had more depressive episodes with atypical features including increased appetite, sleep, and weight gain, more frequent lifetime depressive episodes, and less likelihood of family history of psychiatric disorders. There was no significant difference in the pattern of psychotropic prescription between the 2 groups. Conclusions: There are important differences in the demographic and clinical features of comorbid dysthymia in Chinese MDD patients compared with previous reports. The clinical profile found in this study has implications for treatment decisions.